A SYSTEMATIC LITERATURE REVIEW OF PROJECT-BASED LEARNING INTEGRATED WITH STEM EDUCATION: EXAMINING IMPLEMENTATION STRATEGIES, OUTCOMES, AND CHALLENGES - Auliyani, Chaeriyatun Nissa; Arianto, Fajar; Kholidya, Citra Fitri (Jurnal Visi Ilmu Pendidikan, 2025)
This systematic literature review (SLR) examines the integration of Project-Based Learning (PjBL) with Science, Technology, Engineering, and Mathematics (STEM) education over the past five years (2019-2024). It aims to address the implementation strategies, outcomes, and challenges associated with this educational approach. Despite the growing interest in PjBL and STEM, there are notable gaps in understanding the practical application and effectiveness of combined methodologies in diverse educational settings. This SLR identifies common implementation issues, evaluates the impact on student learning outcomes, and highlights recurring challenges faced by educators. The findings suggest that while PjBL integrated with STEM offers significant benefits, such as enhanced engagement and problem-solving skills, there are ongoing concerns regarding resource constraints and teacher preparedness. This review provides insights for educators and policymakers to improve integration practices and suggests areas for future research to address identified gaps and challenges.